Setting the Stage for Trust and Strategic Integration in Japanese-U.S. Cooperative Alliances - Johnson, Jean L.; Cullen, John B.; Sakano, Tomoaki; Takenouchi, Hideyuki (Journal of International Business Studies, 1996)
This study investigated the formation and outcomes of trust between partners in a specific form of strategic alliance not often studied, the non-equity-based international cooperative alliance (ICA). Because a component of the investigation involved the reciprocal effects of trust in the ICA relationship, dyadic data were gathered from Japanese and U.S. partners in 101 ICAs based in Japan. Results showed that partner cultural sensitivity is an important contributor to trust building for both sides of the dyad. Complementarity with partner contributed to trust for the U.S. but not for the Japanese. Similarity between ICA partners led to trust for the Japanese but not the U.S. partner. The results also showed strong reciprocal effects of trust in the relationship, and that trust of the ICA partner leads the individual firm to integrate the ICA into its own strategic framework.